State of the art of artificial intelligence in internal audit context - Couceiro, B. (2020)
Artificial intelligence (AI) is a technological field that stands out for what can do and for the advantages that can provide to various sectors of activity. An internal audit could benefit from the introduction of AI in its tasks, namely though the automation of audit processes that make it faster and more efficient allowing an increase in the degree of complexity of the tasks that internal auditors may perform. This will enhance the skills of internal auditors in fields like the determination of business processes and associated risks and controls in anticipated detection of fraud and the following up of anomalies in real-time. This article features a set of technologies of AI and the set of benefits it adds to the internal audit. Two models of internal audit applied to artificial intelligence demonstrate how internal audit and internal auditors must adapt to the new reality of AI, by not losing their purpose and by bringing benefits to organizations.